Transformational Leadership of Local Administrators Affecting Efficiency Administration of Local Administrative Organizations in Narathiwat Province - Absee, Ab-dulrormarn; Sareemasae, Ibrahim (Interdisciplinary Academic and Research Journal, 2023)
Transformative leadership is therefore viewed as a holistic process and involves the actions of leaders at different levels in the subdivisions of an organization, stimulating involvement in making important decisions, stimulating competitive thinking, awareness of relevant information, and fostering cooperation and teamwork. Thus, this research aims to study the transformational leadership of local administrative organization administrators affecting the administrative efficiency of local administrative organizations in Narathiwat Province. To study the level of transformational leadership of local government executives in Narathiwat Province and to study the level of administrative efficiency of local government organizations in Narathiwat Province. using quantitative research methods The study population consisted of government personnel, 89 local administrative organizations in Narathiwat Province, consisting of 1 provincial administrative organization, 3 town municipalities, 13 sub-district municipalities72 sub-district administrative organizations including government personnel, local government organizations A total of 727 people used the ready-made tables of Krejcie and Morgan to determine the proportion of the population equal to 0.5, the tolerance level was 5% and the confidence level was 95%. Several 347 people data were collected using a questionnaire. Data were analyzed by mean and standard deviation. The results showed that the Level of Opinions on Transformative Leadership of Local Administrators in Narathiwat Province Overall was at a high level. with an average of 4.26. with the highest mean of 4.31, followed by individual considerations with an average of 4.26. with a mean of 4.25 and intellectual stimulation The lowest mean was 4.23, respectively. Overall, it was at a high level. has an average of 4.24When considering each aspect, it was found that public administration was efficient and worthwhile in terms of the state's mission. with the highest average of 4.28, followed by public administration for the benefit of the people's happiness with an average of 4.26. has an average of 4.26facilitating and responding to the needs of the people with an average of 4.26. Public administration to achieve the mission of the state. with an average of 4.25. Improving the missions of government agencies with an average of 4.22 and evaluation of official performance with the smallest mean of 4.21 respectively Transformational Leadership of Local Administrators Affects Administrative Efficiency in Local Administrative Organizations in Narathiwat Province Ideological Influence inspiration intellectual stimulation Individual considerations Able to jointly predict the efficiency of administration of local administrative organizations in Narathiwat Province at 43.80 percent with a statistical significance at the .05